2016
DOI: 10.15390/eb.2016.6114
|View full text |Cite
|
Sign up to set email alerts
|

Examining Department Chairs’ Needs in Performing Academic Leadership in Turkish Universities

Abstract: KeywordsWhile the educational leadership literature is replete with studies focusing on leadership practices at K-12 level, higher education institutions all over the world do not receive their share from this intense scholarly interest. This is the case with Turkish higher education institutions too. Starting from this point of view, the purpose of this study is to examine department chairs' needs in performing academic leadership. To this end, the study was designed as a qualitative inquiry. In order to reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
0
9
0
8
Order By: Relevance
“…Unlike the results of the study, they stated that the displeasing factors for the leaders are inefficient meetings, constantly travelling, taking no result, time consuming activities such as over reporting, performance management system of the staff and budget management. According to Bellibaş et al (2016), while academic leaders were pointing out the difficulties they encountered, they stated that the fact that they do not have power during the staff recruitment and instead only deans and rectors being authorized affect themselves negatively.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the results of the study, they stated that the displeasing factors for the leaders are inefficient meetings, constantly travelling, taking no result, time consuming activities such as over reporting, performance management system of the staff and budget management. According to Bellibaş et al (2016), while academic leaders were pointing out the difficulties they encountered, they stated that the fact that they do not have power during the staff recruitment and instead only deans and rectors being authorized affect themselves negatively.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…It was observed that when the difficulties the leaders in higher education encountered with were studied, the prominent ones were financing problems, socio-cultural structures, problems about personell and students, the difficulties about the autonomy of higher educational institutions and academic freedom (Bellibaş, Özaslan, Gümüş, & Gümüş, 2016;Odhiambo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature review above, ALC did not receive much attention from scholars in the context of higher education (Bellibas et al, 2016;Radwan et al, 2020). There was still lack of investigations regarding LC in terms of the personal and required skills of academic leaders in Saudi Higher Education (Albutti, 2014;Radwan et al, 2020).…”
Section: The Current Status Of Studies Related To Academic Leadershipmentioning
confidence: 99%
“…Indeed, there were also only a few studies that compared gender differences of academic leadership positions in Saudi Arabia (Albutti, 2014;Almaki et al, 2016). Generally, there were not many studies done about leadership in higher education in many countries (Bellibas, Özaslan, Gümüs, & Gümüs, 2016;Gmelch, 2013;Radwan et al, 2020). The current investigation found a gap in the literature where there are still no systematic strategies of the ALC in Saudi higher education.…”
Section: Introductionmentioning
confidence: 99%
“…Dolayısıyla, buradaki yöneticilerin de teknolojik gelişmelerin hızına ayak uyduran, yeni fikirleri destekleyen ve toplum ihtiyacına yönelik gerekli bilgileri öğretim programına dahil etmeyi başaran kişiler olması beklenmektedir. Shaw'a (2012) (Bellibaş, Özaslan, Gümüş, & Gümüş, 2016;Bryman, 2007;Dimici, Seggie, Hacıfazlıoğlu, & Caner, 2016) (Yin, 2009, s. 18) biçiminde desenlenmiştir.…”
Section: Introductionunclassified